Bretton Woods di Era Globalisasi: Kritik dan Reformasi - Fadilla Jamila; Wahyu Hidayat; Melantik Rompegading (Sawerigading Law Journal, 2025)
The two Bretton Woods institutions, the International Monetary Fund (IMF) and the World Bank, have been pillars of global financial governance since 1944. However, entering the 21st century, the relevance of these two institutions faces significant challenges due to globalization. This study aims to analyze the various challenges and criticisms facing the IMF and the World Bank, as well as to disseminate the effectiveness of their reform efforts. Using normative legal research methods through a contextual approach, this paper examines relevant literature and regulations related to the operations of international financial institutions. The results indicate six major problems within these institutions: the unfairness of the quota system, the dominance of developed countries (especially the United States), the lack of representation of developing countries, the controversy surrounding neoliberal loan conditionality, the threat from new regional financial institutions (such as the NDB and AIIB), and the issue of loan resource stability. Although the IMF and World Bank have undertaken reform efforts, such as adjusting loan conditions and increasing general quotas, these changes are deemed to have failed to address the root causes. The dominance of the United States remains a major challenge to the institutions' evolution. This study concludes that fundamental reforms are needed, including a review of the quota system and increased space for developing countries, to ensure the Bretton Woods Institutions remain relevant in maintaining global economic stability in the future.